The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12870-019-1838-3
|View full text |Cite|
|
Sign up to set email alerts
|

24-Epibrassinolide promotes NO3− and NH4+ ion flux rate and NRT1 gene expression in cucumber under suboptimal root zone temperature

Abstract: Background Suboptimal root zone temperature (RZT) causes a remarkable reduction in growth of horticultural crops during winter cultivation under greenhouse production. However, limited information is available on the effects of suboptimal RZT on nitrogen (N) metabolism in cucumber seedlings. The aim of this study is to investigate the effects of 24-Epibrassinolide (EBR) on nitrate and ammonium flux rate, N metabolism, and transcript levels of NRT1 family genes under subo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…A number of defense-related genes, such as those encoding ascorbate/glutathione, CAT, and POD, are upregulated in ALA-treated bluegrass seedlings under osmotic stress. These findings are in line with those of previous studies, in which exogenous ALA upregulated antioxidant enzyme activities and reduced ROS and MDA accumulation in cucumber seedlings under low-temperature stress [8,10,12,33]. Thus, it can be concluded that exogenous ALA application increased tolerance to low-temperature and weak-light stress, and stabilized ROS and MDA accumulation, thus enhancing cucumber seedling growth (Figure 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A number of defense-related genes, such as those encoding ascorbate/glutathione, CAT, and POD, are upregulated in ALA-treated bluegrass seedlings under osmotic stress. These findings are in line with those of previous studies, in which exogenous ALA upregulated antioxidant enzyme activities and reduced ROS and MDA accumulation in cucumber seedlings under low-temperature stress [8,10,12,33]. Thus, it can be concluded that exogenous ALA application increased tolerance to low-temperature and weak-light stress, and stabilized ROS and MDA accumulation, thus enhancing cucumber seedling growth (Figure 1).…”
Section: Discussionsupporting
confidence: 92%
“…In cucumber seedlings, significantly enhanced activities of SOD, POD, CAT, APX (Ascorbate peroxidase), and GR (Glutathione reductase), and reduced ROS and MDA accumulation, are observed under ALA treatment combined with low-temperature stress [10]. Previous studies have reported that ALA activates the plant defense system and defense-related genes, such as genes encoding SOD, POD, CAT, and APX, in rice and strawberry under osmotic and photodynamic stresses and reduce overproduction of ROS and MDA [31][32][33]. ALA is a precursor of heme biosynthesis, and CAT, POD, and APX contain a heme prosthetic group [14], which might be the reason that antioxidant enzyme activities were stimulated in ALA-treated seedlings ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The same sizes of plants were selected after 15 days after seeds germination, to determined height and hypocotyl diameter using ruler and digital venire caliper respectively as described by Anwar et al (2019). To determine fresh and dry weight, roots and shoots were separated and weighted as as described by Bai et al (2016).…”
Section: Measurement Of Plant Growth Parametersmentioning
confidence: 99%
“…Cucumber (Cucumis sativus. L) is important economic vegetable crop, it is originated from southern Asia, and widely cultivated in greenhouse during winter and summer seasons, as reported by Anwar et al (2019). Because of high nutritional value, cucumber is very commonly cultivated and consumed all around the globe and mostly in China (FAO, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two innovative rapid-breeding approaches, IMGE (haploid-inducer mediated genome editing) and Hi-Edit (haploid induction-edit), which combine haploid induction with CRISPR/Cas9-mediated genome editing was used to introduce desirable traits into elite inbred lines within two generations, avoiding the time-consuming crossing and back-crossing processes [180]. The MiMe phenotype in rice can be reproduced by the simultaneous editing of OsSPO11-1, OsREC8, and OsOSD1, suggesting that different sets of genes involved in meiosis can be manipulated to create the same phenotype [181,182]. Thus, an important benefit of genome editing tools is the ability to integrate complex features that cannot be introduced through traditional enhancement techniques.…”
Section: Recent Progresses In Genome Editing For Crop Improvementmentioning
confidence: 99%